2017
DOI: 10.1177/0890334417737294
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Practices and Barriers to Implementing the Ten Steps to Successful Breastfeeding in Mississippi Hospitals

Abstract: Breastfeeding practices in Mississippi hospitals need to be improved. New policies need to be established in Mississippi to encourage hospitals to adopt the Ten Steps policies and practice in the maternity and birthing units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…There are several achievable steps that can be taken to optimize communication concerning the importance of the BFHI with policymakers and legislators. A structural systematic approach based on the socio‐ecological model for breastfeeding practices may be useful to initiate this communication . This model fosters change in breastfeeding rates at multiple levels, including the individual (breastfeeding education), interpersonal (breastfeeding support programs), institutional (breastfeeding practices inside health facilities), and policy levels (public policies and state laws related to breastfeeding).…”
Section: Health Care Professionals As Key Change Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are several achievable steps that can be taken to optimize communication concerning the importance of the BFHI with policymakers and legislators. A structural systematic approach based on the socio‐ecological model for breastfeeding practices may be useful to initiate this communication . This model fosters change in breastfeeding rates at multiple levels, including the individual (breastfeeding education), interpersonal (breastfeeding support programs), institutional (breastfeeding practices inside health facilities), and policy levels (public policies and state laws related to breastfeeding).…”
Section: Health Care Professionals As Key Change Agentsmentioning
confidence: 99%
“…An advocacy intervention that focuses on BFHI implementation could be effective for changing state legislation and hospital practices on breastfeeding. Several studies have shown that providing support through this level is one of the key factors to improve breastfeeding practices and policies in many countries . Advocating for policy is one of the approaches that can be used to address the BFHI at the policy level.…”
Section: Health Care Professionals As Key Change Agentsmentioning
confidence: 99%
See 3 more Smart Citations